α-Glucosidase and α-Amylase Inhibition Activities of Sarcococca coriacea Hook. And Sarcococca wallichii Staph. of Nepalese Origin - Baral, Janaki; Shrestha, Dipesha; Adhikari, Achyut (Journal of Nepal Chemical Society, 2022)
Diabetes mellitus is being severe health problem globally with an increasing number of patients every day. Due to the lack of effective and non-toxic medicine to cure diabetes, plants that are used in ethnomedicine may be a good source for antidiabetic drug discovery.  Plants of the Sarcococca genus are medicinally important and are used by local people for managing many diseases including diabetes. In the course of our continuous search of antidiabetic plants and pure compounds,  in vitro α-glucosidase, and α-amylase inhibition activity along with the antioxidant activity of methanolic extract of S. coriacea leaf ( Sc-A), S. coriacea stem (Sc-B), and dichloromethane fraction of methanolic extract of Sarcococca wallichi (Sw-D) were carried out. The research revealed dicholoromethane fraction of S. wallichii (Sw-D) with good inhibition of α- amylase enzyme (IC50= 53.79 ± 2.50), whereas Sc-B inhibits α-glucosidase (20.97±2.37) effectively. Similarly, Sc-A showed significant antioxidant activity with IC50=24.56±3.3. The total phenolic content on Sc-A and Sc-B was calculated as 151.35±4.42 mg GAE/g and 86.22±1.59 mg GAE/g whereas the total flavonoid content on Sc-A and Sc-B was found to be 21.61±4.88 mg QE/g and 24.09±4.02 mg QE/g respectively. Similarly, total phenolic and total flavonoid content on Sw-D were found to be 85.26±3.16 mg GAE/g and 21.57±1.26 mg QE/g. To the best of our knowledge, this is the first report of α-glucosidase and α-amylase inhibition activity in these plants. This research work has scientifically supported the use of these plants to manage diabetes by local people and has explored new plants for antidiabetic drug discovery research.